Effect of using Spirulina platensis in place of vitamin mineral premix in feed on the performance of broiler (Bangladesh Journal of Animal Science, 2021)
Feed of commercial broiler fortified by the external sources of vitamin and minerals which is expensive and increase the cost of feed. Blue green algae (Spirulinaplatensis) would be an alternative to those synthetic micronutrients after production in laboratory scale was studied in broiler.Spirulinaplatensiswas cultured in inorganic media contained macronutrients NaHCO3, K2HPO4, NaNO3, K2SO4, NaCl, MgSO4.7H2O, CaCl2, and FeSO4.2H2O and micronutrient solution containing H3BO4, MnCl2.4H2O, ZnSO4.7H2O, CuSO4.5H2O, MoO3, CoCl2.6H2O. Media was autoclaved and Spirulinawas cultured for 12 hours lighting with continuous aeration for 15 days to use in poultry feed. Day old broiler chick (180) was reared offering starter mash diet for 7 days. Birds were divided into 6 groups having 30 birds in each (10 per cage). Birds were offered 1. Control diet, 2. 75% premix+25% Spirulina, 3. 50% premix+50% Spirulina, 4. 25% premix+75% Spirulina, 5. 0% premix+100% Spirulina and 6. 0% premix+0% Spirulina (negative control). Spirulinawas calculated on DM basis added minerals in the media. After 21 days (28 day old) final body weight was 1039, 1070, 1044, 1065, 1117 and 893 g/bird in group 1, 2, 3, 4, 5 and 6 where higher (P